A retrospective study of sedation and analgesic requirements of pediatric patients on extracorporeal membrane oxygenation (ECMO) from a single-center experience. (April 2017) - Anton-Martin, Pilar; Modem, Vinai; Taylor, Donna; Potter, Donald; Darnell-Bowens, Cindy
Introduction: The purpose of this study is to describe the sedative and analgesic requirements identifying factors associated with medication escalation in neonates and children supported on ECMO. Method: Observational retrospective cohort study in a tertiary pediatric intensive care unit from June 2009 to June 2013. Results: One hundred and sixty patients were included in the study. Fentanyl and midazolam were the first line agents used while on ECMO. Higher opiate requirements were associated with younger age (p=0.01), thoracic cannulation (p=0.002), the use of dexmedetomidine (p=0.007) and prolonged use of muscle relaxants (p=0.03). Higher benzodiazepine requirements were associated with younger age (p=0.01), respiratory failure (p=0.02) and the use of second line agents (p=0.002). One third of the patients required second line agents as adjuvants for comfort without a decrease in opiate and/or benzodiazepine requirements. Conclusions: Providing comfort to subpopulations of pediatric ECMO patients seems to be more challenging. The use of second line agents did not improve comfort in our cohort. Prospective studies are required to optimize analgesia and sedation management in children on ECMO.